IMPLEMENTASI ECOPRINT MENGGUNAKAN TEKNIK POUNDING PADA FASE FONDASI (5-6 TAHUN) DI TK SANTA MARIA SINTANG - Fransiska Fransiska; Sudarto Sudarto; Adpriyadi Adpriyadi (STKIP Persada Khatulistiwa Sintang, 2023)
The aims of this study were to describe: planning, implementation and evaluation of ecoprint implementation using pounding techniques in the foundational phase (5-6 years) at TK Santa Maria Sintang. This study uses a qualitative approach with a case study. Data collection techniques used were observation, interview, and document. The subjects in this study consisted of four teacher and fourty one students of B1 and B2 is at foundational phase. The data analysis technique used was Miles and Huberman's data analysis. The results of the study show that: planning for implementing ecoprint using the pounding technique begins with holding a meeting first between teachers and parents, watching videos on YouTube about ecoprint using the pounding technique to increase knowledge and provide equipment for ecoprint activities; The implementation of ecoprint using the pounding technique was carried out for 2 weeks starting from asking parents to prepare 3 leaves related to local wisdom such as paku kubuk (nephrolepis exaltata), sabang merah (cordyline fruticosa) and several leaves around the student's residence as well as joint ecoprint project practice activities between teacher and student; The evaluation of the implementation of ecoprint using the pounding technique is that the ecoprint project using the pounding technique was successfully implemented by TK Santa Maria Sintang and the results of the ecoprint project were displayed at the driving school's P5 expo and during the visit of the Director General of GTK to TK Santa Maria Sintang.